Ketahanan Beberapa Varietas Padi Lokal Sumatera Barat terhadap Virus Penyebab Penyakit Tungro: english - Liswarni, Yenny; Martinius, Martinius; Nurbailis, Nurbailis (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2019)
Tungro disease is one of the obstacles to increasing national rice production. The use of resistant varieties is a component to control the virus that is environmentally friendly and easily accepted because it does not require additional costs. This study aimed to determine the resistance of nine rice varieties commonly planted by farmers against the tungro. The study was conducted in a greenhouse, and the source of the tungro virus inoculum was taken from the Lintau area of ??West Sumatra Province. The results showed that of the nine varieties tested, IR 42 was resistant to the tungro attack, seven others were classified as moderate, and one variety was classified as vulnerable. The moderate resistant varieties were Anak Daro, Cisokan, Cantik Manih, Saganggam Panuah, Junjuang, Kuriek Kusuik, and Caredek Merah. In contrast, the variety that classified as vulnerable was Batang Sungkai due to the symptoms of attack more clearly than on other varieties, the fastest of a period of symptoms appear (10.15 days), the highest disease incidence (80.62%) with a disease index of 7.65.